Controlled field trials of paratyphoid B vaccine and evaluation of the effectiveness of a single administration of typhoid vaccine - Hejfec, L. B. (1968)
In 1963 and 1964 field trials were organized in the USSR for the purpose of evaluating the effectiveness of paratyphoid B vaccine. An opportunity was thereby afforded to assess the effectiveness of a single administration of typhoid vaccine, used as the preparation administered to the paratyphoid control group of 89 046 persons. Similarly, the control group used for assessing the effectiveness of the typhoid vaccine was the group of 86 620 persons inoculated with the paratyphoid vaccine. It was established that it is, in principle, possible to immunize people effectively against paratyphoid B by administering heat-killed paratyphoid B vaccine prepared from an aerated broth culture. It was found that the protective effect of the vaccine depends upon the size of the dose and the number of times it is administered. A protective effect was produced when a dose of 6 × 10(8) organisms was administered to persons from 7 to 16 years of age. Two inoculations of the paratyphoid B vaccine ensured protection over the 30 months that the observations lasted, whereas a single administration only conferred protection for up to one year. It was also confirmed that it is possible to obtain a protective effect with a single administration of a heat-killed typhoid vaccine prepared from an aerated broth culture. A single administration of the typhoid vaccine had a less marked protective effect (index of effectiveness 58%) than 2 administrations, a fall in the level of the protection conferred occurring during the year after immunization. The frequency and intensity of general and local reactions were identical for equal doses of typhoid and paratyphoid B vaccine.